A Formulation–Process–Product Integrated Design Method for Accelerating Pharmaceutical Tablet Development via the High-Shear Wet Granulation and Tableting Route - Zichen Liang; Xuefang Tang; Liping Chen; Yifei Liu; Shuying Zhao; Xiao Ma; Gan Luo; Bing Xu (Pharmaceutics)
Background/Objectives: Tablet is the most popular oral solid dosage form, and high-shear wet granulation and tableting (HSWGT) is a versatile technique for manufacturing tablets. The conventional pharmaceutical development for HSWGT is carried out in a step-by-step mode, which is inefficient and may result in local optimal solutions. Inspired by the co-design philosophy, a formulation–process–product integrated design (FPPID) framework is innovatively brought forward to enable the target-oriented and simultaneous exploration of the formulation design space and the process design space. Methods: A combination of strategies, such as a material library, model-driven design (MDD), and simulation-supported solution generation, are used to manage the complexity of the multi-step development processes of HSWGT. The process model was developed at the intermediate level by incorporating dimensionless parameters from the wet granulation regime map approach into the process of the partial least square (PLS) model. The tablets tensile strength (TS) and solid fraction (SF) could be predicted from the starting materials’ properties and process parameters. The material library was used to diversify the model input and improve the model’s generalization ability. Furtherly, the mixture properties calculation model and the process model were interconnected. Results: A four-step FPPID methodology including the target definition, the formulation simulation, the process simulation, and the solution generation was implemented. The performance of FPPID was demonstrated through the efficient development of high-drug-loading tablets. Conclusions: As a holistic design method, the proposed FPPID offers great opportunity for designers to handle the complex interplay in the sequential development stages, facilitate instant decisions, and accelerate product development.